2020
DOI: 10.1002/ceat.202000113
|View full text |Cite
|
Sign up to set email alerts
|

Isothermal by Design: Comparison with an Established Isothermal Nucleation Kinetics Analysis Method

Abstract: The nucleation kinetics of the alpha form of p‐aminobenzoic acid from ethanolic and aqueous solutions is examined through a comparative examination of temperature‐jump and anti‐solvent drown‐out isothermal crystallization methodologies. Analysis of the data reveals the measured induction times, and the calculated effective interfacial tensions as a function of the supersaturation show broadly equivalent behavior for the aqueous‐ethanol mixed‐solvent drown‐out and temperature‐jump ethanol solution systems, conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…A previous study demonstrated that, in solubility mismatched mixed-solvent solutions, such as the system studied here, the local solvation environment of a nucleating solute would be likely to be dominated by the strongest solvating solvent, due to the much higher intermolecular interaction strengths. 17 Therefore, for the current procedure the interactions of toluene molecules with eicosane were calculated first, followed by the acetone molecules. Whilst this molecular modelling technique provides an attractive and representative molecular-scale assessment as to likely solute : solvent ordering within the solution, it is clearly limited by the fixed interaction procedure imposed by the chosen grid size that neither directly allows for the effects of molecular conformational flexibility nor deals with the random solute : solvent interactions, which might be expected within a mixed-solvent/antisolvent system, as studied here.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…A previous study demonstrated that, in solubility mismatched mixed-solvent solutions, such as the system studied here, the local solvation environment of a nucleating solute would be likely to be dominated by the strongest solvating solvent, due to the much higher intermolecular interaction strengths. 17 Therefore, for the current procedure the interactions of toluene molecules with eicosane were calculated first, followed by the acetone molecules. Whilst this molecular modelling technique provides an attractive and representative molecular-scale assessment as to likely solute : solvent ordering within the solution, it is clearly limited by the fixed interaction procedure imposed by the chosen grid size that neither directly allows for the effects of molecular conformational flexibility nor deals with the random solute : solvent interactions, which might be expected within a mixed-solvent/antisolvent system, as studied here.…”
Section: Methodsmentioning
confidence: 99%
“…[13][14][15] Crystallisation from mixed-solvent solution systems can be directed, either through cooling of an initial solvent blend 7,16 or through antisolvent crystallisation. 15,17 Both routes require miscible solvents, with the latter requiring significant differences in the solubility of the solute between the solvent and antisolvent, the addition of which lowers solute solubility and hence generates supersaturated conditions. In the design of mixed-solvent crystallisation processes, it is helpful to have developed workflows for the characterisation of the solubility and solution properties over the full range of compositions used and, through this, optimise the process parameters to ensure the desired crystal product characteristics.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The crystals prepared by this method are relatively tiny, and their dimensions do not increase significantly during AC . Compared to traditional cooling or evaporative crystallization methods, the precipitation process is typically quick, and the induction period is much shorter . The purification effect is typically poor, and the impurities are challenging to separate .…”
Section: Introductionmentioning
confidence: 99%